2020
DOI: 10.1177/0301574220960307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lip Position in Esthetically Pleasing Profiles Using Different Reference Lines: A Photographic Study

Abstract: The aim of this article is to assess the lip position using five different reference lines in individuals with a pleasing profile. A cross-sectional study was conducted with a sample size of 200 subjects chosen from the local North Indian population. Non-growing subjects, between the age group of 18 years and 25 years with a pleasing facial profile were screened for the study via a questionnaire-based method to confirm their North Indian ancestry (history of past two generations from North India). All subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…The increase in length of the upper and lower lips in males was twice as large as in females, similar to the studies by Arnett, Kalha, Lalitha, Hamdan, and Yan, et al 9,[23][24][25] A study of soft-tissue growth in 7-18-year-old subjects conducted by Nanda reported that the length of upper lip measured from subnasal to stomion increased up to 2.7 mm in males and 1.15 mm in females. Meanwhile, the height of lower lip (measured from stomion of the lower lip to the B point of soft tissue) increased up to 4.2 mm in males and 1.5 mm in females.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The increase in length of the upper and lower lips in males was twice as large as in females, similar to the studies by Arnett, Kalha, Lalitha, Hamdan, and Yan, et al 9,[23][24][25] A study of soft-tissue growth in 7-18-year-old subjects conducted by Nanda reported that the length of upper lip measured from subnasal to stomion increased up to 2.7 mm in males and 1.15 mm in females. Meanwhile, the height of lower lip (measured from stomion of the lower lip to the B point of soft tissue) increased up to 4.2 mm in males and 1.5 mm in females.…”
Section: Discussionsupporting
confidence: 90%
“…The sagittal position of the upper lip in different skeletal malocclusions in the study can be assessed better with the Sushner's S2 line because this line passes through stable and consistent anatomical landmarks as it is adjacent to the skeletal structure and not influenced by the nose. 9 Similar study 10 was also conducted in Indian population aged 18-26 years.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Charles Tweed was one of the first people to show interest in the facial proportion and harmony of a patient within the orthodontic treatment [3]. There are a lot of methods of profile aesthetics assessment in orthodontics, and some of them are based on Ricketts' E lines, Merrifield's Z lines or Steiner's S lines [4,5,6].…”
Section: Introductionmentioning
confidence: 99%